[Ru(η6-p-cymene)(N^O 8-hydroxyquinoline)(PTA)] complexes as rising stars in medicinal chemistry: synthesis, properties, biomolecular interactions, in vitro anti-tumor activity toward human brain carcinomas, and in vivo biodistribution and toxicity in a zebrafish model. Issue 21 (24th May 2022) - P. K., Anuja; Roy, Nilmadhab; Das, Utpal; Varddhan, Seshu; Sahoo, Suban K.; Paira, Priyankar
Abstract : DNA-targeting half-sandwich [Ru(η 6 - p -cymene)(N^O 8-hydroxyquinoline)(PTA)] complexes have been developed for human brain cancer cell therapy. Abstract : Herein, we have introduced a class of half-sandwich [Ru(η 6 - p -cymene)(N^O 8-hydroxyquinoline)(PTA)] complexes for brain cancer therapy. Among all the complexes, [RuL3PTA ] and [RuL4PTA ] exhibited excellent cytotoxicity profiles against T98G, LN229, and U87MG cancer cells. Notably, the antiproliferative activities of the relevant complexes were also supported by neurosphere, DNA intercalation, agarose gel electrophoresis, and time-dependent ROS detection assay studies. Detailed molecular assays were obtained via real-time reverse transcription (RT)-polymerase chain reaction (PCR) experiments. Moreover, the in vivo biodistribution of the [RuL4PTA ] complex in different organs and the morphological patterns of zebrafish embryos due to toxic effects have been evaluated.